Feasibility of training nurses in motivational interviewing to improve patient experience in mental health inpatient rehabilitation: a pilot study. Issue 4 (May 2017) - Bunyan, M.; Crowley, J.; Smedley, N.; Mutti, M‐F.; Cashen, A.; Thompson, T.; Foster, J.
Accessible summary: What is known on the subject?: Recently, concerns have been raised about how well United Kingdom National Health Service nurses care for their patients and their level of compassion. Motivational interviewing (MI) is an established approach to helping people make positive behaviour changes, through directive, person‐centred counselling within a collaborative relationship between clinician and recipient. Based on evidence that MI may influence nursing practice positively, an investigation into the feasibility of training nurses on mental health inpatient rehabilitation wards ('rehabilitation') in MI to improve patient experience was reported. What this paper adds to existing knowledge?: This pilot study demonstrates that training rehabilitation nurses in MI is feasible and provides preliminary evidence suggesting that a larger study to examine efficacy is warranted, including a calculation of sample size required to draw robust statistical conclusions. Nurses evaluated the training as highly relevant to their work. Patients responded well to interviews and focus groups with support from experts‐by‐experience; they were generally fairly satisfied with the rehabilitation ward and slight improvements in their experience were found following MI training for nurses but not at 6‐month follow‐up. What are the implications for practice?: Rehabilitation nurses may face conflicting demands between ensuring patients with severe difficulties meet their basic needs and working with them to develop greater independence. Qualitative findings question whether nurse–patient interactions are fully valued as nursing interventions in inpatient rehabilitation. Learning MI might be a useful way of helping nurses think in detail about their interactions with patients and how to improve communications with their patients. The principles of MI should be incorporated into pre‐registration training. Abstract: Introduction: There is limited research addressing the experiences of patients in inpatient rehabilitation (rehabilitation), who often spend long periods in hospital, and the nursing approaches utilized. Aim: Based on evidence that motivational interviewing (MI) may improve nursing practice, this was a pilot study evaluating the feasibility of training rehabilitation nurses in MI and measuring patient experience. Method: Nurses underwent training and supervision focusing on MI spirit. Quantitative and qualitative measures were taken pretraining, 2 months post‐training and 8 months post‐training. Expert‐by‐experience research assistants facilitated patients' participation in the study. Results: This study showed that training rehabilitation nurses in MI was feasible and relevant to their work. Patients participated in interviews and focus groups with support and potential improvements that require further empirical investigation in patient experience were found following the MI training. Discussion: This pilot study establishes the feasibility of a larger study addressing efficacy. Tentative qualitative findings question whether interactions between nurses and patients are valued in rehabilitation and support MI as a promising skill set for rehabilitation nurses. Implications for practice: Bringing MI into inpatient rehabilitation provoked reflection on nursing practice. Dilemmas for nurses about balancing safety with promoting autonomy and communicating constructively with patients emerged as important.